A study of job stress among professional accountants working in selected public accounting firms : A Malaysian case - Md Ali, Azham (Universiti Utara Malaysia, 1992)
The study replicates and extands earlier studies on job in public accounting conducted in the United States (Gaertner and Ruhe, 1981) and Britain (Lyall, 1984) it is done through an extensive review of literature on job stress and field studying using the same questionnaire as utilized in the two earlier studies with only slight modifications are made to suit the Malaysia context. The study seeks answer to what may be the sources of stress, psychological outcomes and moderators of stressful situations in selected public accounting firms and wheter there exist significant linear relationships between the job stressors and mental strains.